2011
DOI: 10.2174/138920111794480552
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Cardiovascular Function in DOCA-Salt Hypertensive Rats

Abstract: The phytoalexin resveratrol (3,4',5-trihydroxy-trans-stilbene) may attenuate cardiovascular disease in man. This study has determined whether treatment with resveratrol (1 mg/kg/day orally) prevented cardiac fibrosis and the decreased cardiovascular function in the DOCA-salt hypertensive rat as a model of human hypertension. Uninephrectomised rats (UNX) administered DOCA (25mg every 4th day sc) and 1% NaCl in drinking water for 28 days developed cardiac and vascular remodelling. In these DOCA-salt rats, resver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
59
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 0 publications
5
59
1
Order By: Relevance
“…STZ-induced DM is known to increase oxidative stress and subsequently impair endothelial and smooth muscle function in isolated thoracic aortas (51)(52)(53) . Consistent with these findings, we observed significantly reduced endothelium-dependent and endothelium-independent relaxation in thoracic aortic rings isolated from STZ rats.…”
Section: Discussionmentioning
confidence: 99%
“…STZ-induced DM is known to increase oxidative stress and subsequently impair endothelial and smooth muscle function in isolated thoracic aortas (51)(52)(53) . Consistent with these findings, we observed significantly reduced endothelium-dependent and endothelium-independent relaxation in thoracic aortic rings isolated from STZ rats.…”
Section: Discussionmentioning
confidence: 99%
“…These include the following: (i) hypertension (Liu et al 2005;Dolinsky et al 2009;Thandapilly et al 2010;Toklu et al 2010;Wojciechowski et al 2010;Chan et al 2011;Rimbaud et al 2011); (ii) obesity (Louis et al 2011;Qin et al 2012 (Barger et al 2008). There is also one study that reported cardioprotection in an animal model of heart failure (Tanno et al 2010).…”
mentioning
confidence: 99%
“…The average recommended dose of red wine is 2 glasses (approximately 300 mL, which is a conservative estimate), and it has been recently reported that some red wines may contain as much as 40-50 mg resveratrol per litre (Gonçalves and Camara 2011). This would equate to a dose of as much as 15 mg resveratrol in 300 mL of wine, which is slightly lower than that used to improve cardiac structure and function in animal models of ischemic heart disease and hypertension in 2 above-mentioned studies (Chan et al 2011;Lin et al 2008). The dose used in those animal studies was •day -1 (Lin et al 2008;Chan et al 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations